Isolasi Bakteri Termofilik dari Tanah Hutan Mangrove - Fidhia Rara Lande; Wahyu Widayat; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Mangrove forest soil is a habitat and source of diversity of microorganisms, including thermophilic bacteria. The utilization of thermophilic bacteria has been carried out in the pharmaceutical field, especially as a source of raw materials for pharmaceutical products. This study aims to provide an overview of the population of thermophilic bacteria found in mangrove forest soils. Soil samples were obtained by random stratification with a depth of 5-10 cm at 9 points from 3 strata. The isolation media used were Starch Casein Agar (SCA), and the groups of bacteria determined by using the Gram staining method. The selected thermophilic bacteria from mangrove forest soil totaling 64 isolates consisted of Gram-negative that divides into 20 bacilli, 9 cocci, 6 vibrios, and Gram-positive consisted of 26 bacilli, 3 cocci. The highest population of thermophilic bacteria from mangrove forest soils was Gram-negative as many as 35 isolates.